Sanitation and Incidence of Malaria in Urban Areas: A Case Study in Gbawe, Accra - Nyadzi, W.B. (University of Ghana, 2013)
Rapid urbanization in Accra over the years has come with its attendant sanitation and health problems. It is said that the major health problems in urban centers are preventable and communicable diseases attributed to poor environmental sanitation. This study examined the perceived causes of poor sanitary condition and their links with the incidence of malaria in Gbawe. The study also identified the major factors influencing the disposal of household wastes and established the factors which influenced households’ method of disposal of waste. This was undertaken through elicitation of data and information from residents of the area directly with additional information derived from interviews with personnel of Public Health Nurses School Demonstration Clinic and the Waste Management Department in the Ga South Municipality. The survey data collected was analyzed using simple statistical analysis to derive frequencies and means of important variables. Chi-square test was also employed to analyze relationships among variables. Logistic regression analysis was the third method of statistical analysis used in the study and it identified the statistically significant factors that influenced the likelihood of respondents using improved methods of disposal of solid wastes generated in their homes. The results of the study showed that householders perceived attitude problem due to lack of care in proper disposal of wastes, high fees charged at the public dump site and by private waste collection service providers, and weak enforcement of sanitation bylaws by authorities as the major factors responsible for improper disposal of wastes. The majority of the residents did not have toilet facilities in their homes and hence relied on public toilet facilities and the bush or field for disposal of human excreta. With regards to method of solid waste disposal, householders disposed wastes in the public dump and containers, burned them, threw them in the bush or patronized the services of private firms involved in waste collection and disposal. Other results indicated that the probability of using an improved method of disposing solid wastes increased with increasing household income but it decreased with increasing number of household members. The main cause of malaria as perceived by respondents was improper disposal of wastes which served as breeding grounds for mosquitoes which transmitted malaria to humans.
Thesis (MA)-University of Ghana, 2013